2008
DOI: 10.1348/000711006x169991
|View full text |Cite
|
Sign up to set email alerts
|

Influence analysis for the factor analysis model with ranking data

Abstract: Influence analysis is an important component of data analysis, and the local influence approach has been widely applied to many statistical models to identify influential observations and assess minor model perturbations since the pioneering work of Cook (1986). The approach is often adopted to develop influence analysis procedures for factor analysis models with ranking data. However, as this well-known approach is based on the observed data likelihood, which involves multidimensional integrals, directly appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(115 reference statements)
0
2
0
1
Order By: Relevance
“…Several researchers have proposed limited-information methods using the ranking of pairs or triples of choices (Brady, 1989;Chan & Bentler, 1998;Maydeu-Olivares, 1999). Others have proposed fullinformation maximum likelihood methods using Monte Carlo expectation-maximization algorithms (Poon & Lu, 2009;Xu, Poon, & Lee, 2008). Yao and Böckenholt (1999) and Yu (2000) showed that Bayesian Thurstonian ranking models are amenable to Markov chain Monte Carlo (MCMC) algorithms by using data augmentation with Gibbs sampling (Gelfand & Smith, 1990;Tanner & Wong, 1987).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Several researchers have proposed limited-information methods using the ranking of pairs or triples of choices (Brady, 1989;Chan & Bentler, 1998;Maydeu-Olivares, 1999). Others have proposed fullinformation maximum likelihood methods using Monte Carlo expectation-maximization algorithms (Poon & Lu, 2009;Xu, Poon, & Lee, 2008). Yao and Böckenholt (1999) and Yu (2000) showed that Bayesian Thurstonian ranking models are amenable to Markov chain Monte Carlo (MCMC) algorithms by using data augmentation with Gibbs sampling (Gelfand & Smith, 1990;Tanner & Wong, 1987).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Por lo tanto, el análisis de la influencia es considerado como un componente importante en el análisis de un diseño experimental 3 ω . Aunque el análisis de la influencia ha sido durante mucho tiempo un tema importante en varios modelos estadísticos (véase, [3], [4], [2], [5], [6], [7], [8], [9], [10], [11], [12], [13]), se ha trabajado muy poco en los diseños factoriales simétricos, y en particular, en los diseños 3 ω .…”
Section: Introductionunclassified
“…Analysis of ranking data in the Thurstonian framework has received much attention in the behavioural science literature. See Arbuckle and Nugent (1973) for a general parameter estimation procedure, Böckenholt (1992) for a multivariate partial ranking model, Yao and Böckenholt (1999) and Yu (2000) for a Bayesian approach with Gibbs sampler, Brady (1989), Chan and Bentler (1996, 1998), and Yu, Lam, and Lo (2005) for factor analysis models, and Poon and Chan (2002) and Xu, Poon, and Lee (2008) for influence analysis. Moreover, relating the choice of a set of alternatives to the underlying subjective values is a commonly used modelling approach in marketing: see, for example, Currim (1982), Kamakura and Srivastava (1984), Carroll, Soete, and DeSarbo (1990), Harlam and Lodish (1995), Huber and Zwerina (1996) and Sinha and DeSarbo (1998).…”
Section: Introductionmentioning
confidence: 99%